2022
DOI: 10.1111/padm.12845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of local government social media use on citizen compliance during a crisis: Evidence from the COVID‐19 crisis in China

Abstract: Improving citizen compliance is a major goal of public administration, especially during crises. Although social media are widely used by government agencies across the globe, it is still unclear that whether the use of social media can help local governments improve citizen compliance especially during crises. Based on an original daily panel dataset of 189 cities in China during COVID‐19, this study provides empirical evidence for the positive effect that crisis‐related social media posts published by local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…Citizens' engagement with their governors on Twitter was significantly and positively associated with their compliance with stay‐at‐home orders ( p < .01). Consistent with a few recent studies of crisis communication on social media (Han & Baird, 2022; Jiang & Tang, 2022), these results highlight the importance of posting timely and needed information during a crisis. Furthermore, the results reveal that there may be a paradox associated with reputation management during a crisis.…”
Section: Findings and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Citizens' engagement with their governors on Twitter was significantly and positively associated with their compliance with stay‐at‐home orders ( p < .01). Consistent with a few recent studies of crisis communication on social media (Han & Baird, 2022; Jiang & Tang, 2022), these results highlight the importance of posting timely and needed information during a crisis. Furthermore, the results reveal that there may be a paradox associated with reputation management during a crisis.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Heavily politicized crisis communication can influence the public's perception of government responses and their trust in the government and, consequently, their compliance with policy guidance. A few recent studies provided consistent evidence that government crisis messaging on Twitter and other social media platforms could affect citizens' compliance with policies (e.g., Han & Baird, 2022;Jiang & Tang, 2022;Yassin et al, 2022).…”
Section: Crisis Communication Social Media and Public Engagement And ...mentioning
confidence: 98%
“…Compliance costs for disaster assistance applications can be time‐consuming and complex for survivors, some of whom might not have the necessary documents due to damage or loss from the disaster. As noted above, a disaster assistance application website was set up after Winter Storm Uri, but many applicants did not have easy access to a computer or broadband services for these applications, as numerous populations lost power and access to transportation (Busby et al, 2021; Hobby School of Public Affairs at the University of Houston, 2021; Jiang & Tang, 2022; Lee et al, 2021b; Machemer, 2021).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Compliance costs refer to the costs of providing documentation, applying for a service, completing forms, behavioral compliance, and complying with regulations in the application processes. Compliance costs also entail navigating information online, standards of conduct, and meeting governmental demands during crises (Jiang & Tang, 2022). For instance, for those applying to a program for services, there are the costs of completing forms and paperwork, providing documentation of status, the time commitment to apply, and the costs of following program rules and requirements.…”
Section: Theoretical Overview: Administrative Burdensmentioning
confidence: 99%
“…As the Chinese public relied greatly on social media to cope with the pandemic ( Wei et al 2021 ), this was significantly affected by government accounts. Jiang and Tang (2022) revealed that crisis-related social media posts from local governments in China resulted in higher offline citizen compliance during the COVID-19 crisis, illustrating the potential power of government social media accounts.…”
Section: Political Information Seeking From Government Social Media A...mentioning
confidence: 99%